2020
DOI: 10.1186/s13059-020-02161-6
|View full text |Cite
|
Sign up to set email alerts
|

AlphaBeta: computational inference of epimutation rates and spectra from high-throughput DNA methylation data in plants

Abstract: Stochastic changes in DNA methylation (i.e., spontaneous epimutations) contribute to methylome diversity in plants. Here, we describe AlphaBeta, a computational method for estimating the precise rate of such stochastic events using pedigree-based DNA methylation data as input. We demonstrate how AlphaBeta can be employed to study transgenerationally heritable epimutations in clonal or sexually derived mutation accumulation lines, as well as somatic epimutations in long-lived perennials. Application of our meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 64 publications
5
25
0
Order By: Relevance
“…Spontaneous or random errors in the maintenance of methylation lead to ‘epimutation’ and generate single methylation polymorphisms (SMPs) including CG-, CHG-, CHH-SMPs [ 91 ], or differentially methylated regions (DMRs) [ 92 ]. Spontaneous epimutation rates are estimated to be similar across species [ 93 ], with SMPs in the range 1 × 10 −4 to 10 −5 sites/haploid/generation, which is far higher than SNPs (1 × 10 −8 to 10 −9 ) [ 86 ]. In contrast with SMPs, the level of methylation across larger regions is more stable (1 × 10 −5 to 10 −6 sites/haploid/generation) [ 94 , 95 ].…”
Section: Opportunities and Challenges For Crop Improvementmentioning
confidence: 99%
“…Spontaneous or random errors in the maintenance of methylation lead to ‘epimutation’ and generate single methylation polymorphisms (SMPs) including CG-, CHG-, CHH-SMPs [ 91 ], or differentially methylated regions (DMRs) [ 92 ]. Spontaneous epimutation rates are estimated to be similar across species [ 93 ], with SMPs in the range 1 × 10 −4 to 10 −5 sites/haploid/generation, which is far higher than SNPs (1 × 10 −8 to 10 −9 ) [ 86 ]. In contrast with SMPs, the level of methylation across larger regions is more stable (1 × 10 −5 to 10 −6 sites/haploid/generation) [ 94 , 95 ].…”
Section: Opportunities and Challenges For Crop Improvementmentioning
confidence: 99%
“…The WGBS data from the ddm1- epiRILs was analyzed using the Methylstar v1.4 pipeline 75 . Region-level methylation calls were obtained with Methimpute v1.16.0 (200 bp bins, step size = 50 bps, at least 10 cytosines per bin) 76 .…”
Section: Methodsmentioning
confidence: 99%
“…DNA methylation patterns can change either because of failure in maintaining methylation after replication or because of active removal by enzymes (Zhang et al 2018 ). In A. thaliana , it has been reported that CG “germline” epimutations are about five orders of magnitude more frequent than genetic mutations: about 10 −4 vs about 10 −9 per site per haploid genome per generation (Shahryary et al 2020 ).…”
Section: Tools For the Analysis And Characterization Of Cwr Epigeneti...mentioning
confidence: 99%